Prosthetic management of anophthalmic socket with inferior orbital deficiency using custom acrylic ocular prosthesis: a case report - Syahputra, Arman Adrian; Pramudita, Seto; Meidarlina, Ista; Damayanti, Lisda (Universitas Padjadjaran, 2025)
Introduction: The loss of the bulbus oculi can occur due to congenital abnormalities or trauma. In severe trauma cases, enucleation is often necessary, involving the removal of the entire eyeball while preserving surrounding muscle and tissue. However, trauma may also damage the periocular muscles, affecting the fit and mobility of an ocular prosthesis, making rehabilitation more complex. The aim of this case report is to describe the clinical procedure and outcomes of fabricating a custom ocular prosthesis for a post-enucleation patient with compromised periocular muscle support due to trauma, emphasizing the importance of individualized prosthesis design in achieving optimal fit, aesthetics, and patient satisfaction..Case Report: This case presents the fabrication of a custom ocular prosthesis for a 40-year-old male patient who lost his left eye in a motorbike accident seven years ago. He previously used a prefabricated ocular prosthesis, which was uncomfortable, frequently dislodged, and did not fit his eye socket properly, significantly affecting his confidence and daily activities. His occupation as an online motorcycle taxi driver emphasized the need for a stable and aesthetically pleasing prosthesis. The rehabilitation process involved impression-taking with polyvinyl siloxane, wax sclera try-in for contour and retention assessment, acrylic sclera formation, iris and pupil positioning, and final prosthesis placement. Conclusion: This case report highlights the clinical challenges and solutions in managing an anophthalmic socket with inferior orbital deficiency through the use of a custom acrylic ocular prosthesis. The compromised support from the inferior periocular structures necessitated a highly tailored approach to ensure proper prosthesis retention, mobility, and aesthetic harmony. Through meticulous impression-taking, accurate iris positioning, and precise customization, the prosthesis successfully restored facial symmetry, improved patient comfort, and enhanced psychological well-being. This case underscores the importance of individualized prosthetic design in complex ocular rehabilitation cases, particularly those involving post-traumatic muscle loss.